2022
DOI: 10.1111/bph.15838
|View full text |Cite
|
Sign up to set email alerts
|

Host‐directed anti‐mycobacterial activity of colchicine, an anti‐gout drug, via strengthened host innate resistance reinforced by the IL‐1β/PGE2 axis

Abstract: Background and Purpose: To diversify and expand possible tuberculosis (TB) drug candidates and maximize limited global resources, we investigated the effect of colchicine, an FDA-approved anti-gout drug, against Mycobacterium tuberculosis (Mtb) infection because of its immune-modulating effects.Experimental Approach: We evaluated the intracellular anti-Mtb activity of different concentrations of colchicine in murine bone marrow-derived macrophages (BMDMs).To elucidate the underlying mechanism, RNA sequencing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Western blot analysis was conducted as previously described. 32 Briefly, total protein was extracted from lung tissue using PRO-PREP protein extraction solution (#17081, INTRON Biotechnology, Seoul, South Korea) following the manufacturer's instructions. Proteins were quantified, and equal amounts were separated by SDS-PAGE, then transferred onto Immun-Blot™ PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot analysis was conducted as previously described. 32 Briefly, total protein was extracted from lung tissue using PRO-PREP protein extraction solution (#17081, INTRON Biotechnology, Seoul, South Korea) following the manufacturer's instructions. Proteins were quantified, and equal amounts were separated by SDS-PAGE, then transferred onto Immun-Blot™ PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%
“…Sample sizes for this study were established based on prior research, including studies from our group. 32 , 33 , 34 , 35 An a priori power analysis was conducted to confirm the appropriateness of our sample sizes, targeting 80% power and a 0.05 alpha level. This analysis indicated that a minimum of three mice per group would suffice.…”
Section: Methodsmentioning
confidence: 99%
“…Berbamine was shown to activate macrophage autophagy by modulating the ROS/Ca2+ axis, and could efficiently inhibit MTB, demonstrating the advantage of improving the efficacy or shortening the course of treatment in drug-resistant TB ( 114 ). The antigout drug colchicine enhanced macrophage resistance to MTB by modulating NLRP3-dependent IL-1β signaling and COX-2-mediated PGE2 production in macrophages ( 115 ).…”
Section: The Candidates Of Hdt For Mtb Treatmentmentioning
confidence: 99%
“…Colchicine has been a medicine widely used in GA for a long history. 183,184 The incidence of adverse reactions is high since the therapeutic dose of colchicine is close to the toxic dose. 185 For patients with acute gout attacks, it is recommended to accept colchicine treatment in the first dose of 1 mg, 0.5 mg after 1 h, and 0.5 mg after 12 h, with a frequency of once a day or twice a day.…”
Section: Clinical Approaches For Ga Prevalent Drugsmentioning
confidence: 99%